Resilient Libraries. Issue 3 (3rd July 2021) - Garnett, Johanna
ABSTRACT: Hazards, both natural and human induced, have impacted libraries throughout history. With multiple examples across the globe of libraries impacted by a range of hazards and the future prospect of natural hazards occurring in greater strength and frequency, it is important for libraries to consider a changed approach to risk management from a 'response/reactive' focus to 'resilience building'. This paper will demonstrate examples of Australian libraries impacted by a range of natural hazards, discuss the meaning of resilience and increase awareness of a specialist 'Disaster Resilience Toolkit for Libraries' designed to assist libraries in assessing their current resilience levels to natural hazards, specifically flood, fire and earthquake.